2012
DOI: 10.1063/1.4761921
|View full text |Cite
|
Sign up to set email alerts
|

Statistical analysis of kinetic energy entrainment in a model wind turbine array boundary layer

Abstract: For large wind farms, kinetic energy must be entrained from the flow above the wind turbines to replenish wakes and enable power extraction in the array. Various statistical features of turbulence causing vertical entrainment of mean-flow kinetic energy are studied using hot-wire velocimetry data taken in a model wind farm in a scaled wind tunnel experiment. Conditional statistics and spectral decompositions are employed to characterize the most relevant turbulent flow structures and determine their length-sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
62
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 82 publications
(68 citation statements)
references
References 43 publications
(26 reference statements)
5
62
0
Order By: Relevance
“…As expected from other wind tunnel studies for wind energy [36][37][38], positive values of −uv occur above hub height in the wake. This component of the Reynolds shear stresses is associated with the vertical flux of mean flow kinetic energy by turbulence and remediation of the wake.…”
Section: A Turbulence Fieldsupporting
confidence: 55%
See 1 more Smart Citation
“…As expected from other wind tunnel studies for wind energy [36][37][38], positive values of −uv occur above hub height in the wake. This component of the Reynolds shear stresses is associated with the vertical flux of mean flow kinetic energy by turbulence and remediation of the wake.…”
Section: A Turbulence Fieldsupporting
confidence: 55%
“…Figure 2 shows the selected planes as bold dashed lines in the wake of the fourth row of wind turbines. Sample data correspond to measurements at x/D = 0.5, reflecting the near wake where the intermittency is greatest [35], and x/D = 6 in the far wake, where the momentum deficit in the wake has largely recovered and the flow is well-mixed [36]. Turbulence statistics at x/D = 6 represents the flow that would be seen by successive rows of devices.…”
Section: A Wind Turbine Wake: Experimental Datamentioning
confidence: 99%
“…Numerical simulations of flow over large wind farms have suggested that the rate of TKE exchange with less turbulent and faster-moving air aloft determines how the wake region decays (Calaf et al 2010). Wind-tunnel investigations (Hamilton et al 2012) suggest a coupling between the dissipation rate, small-scale turbulence, and the large-scale structures of the flow in the upper portions of the wake.…”
Section: Introductionmentioning
confidence: 99%
“…Results are compared in the wake of the WT and of the AD. The transport equation of the mean-flow kinetic-energy (2) is obtained as by Hamilton et al (2012), with a Reynolds double decomposition of the flow where u i is the time average velocity in the i-direction and K E is the mean-flow average kinetic energy, p is the pressure, and u 0 i u 0 j are the Reynolds stresses. The third term of the right-hand-side of Eq.…”
Section: F Theorymentioning
confidence: 99%